The Effect of Body Practices and Physical Exercise on Sexual Function of Menopausal Women. A Systematic Review with Meta-Analysis - Fausto D.Y.* (2023)
© 2023 Taylor & Francis Group, LLC.Objective: To review randomized clinical trials on Body Practices (BP) and Physical Exercise (PE) in menopausal women and describe their effect on sexual function. Methods: Searches carried out electronically in five databases, with a temporal criterion of 10 years of publication, from August to September 2022. Methodological quality and risk of bias were assessed using the Cochrane collaboration scale and PEDro (Physiotherapy Evidence Database Physiotherapy Evidence Database) scale score. Results: The majority of the studies presented a “'low” or “'uncertain” risk of bias. The instruments for assessing sexual function were heterogeneous. Interventions included mindfulness, relaxation hypnosis, Kegel exercises, yoga, and aerobic exercise, and generally lasted 12 weeks. Seven studies were included, of which six made up the meta-analysis, showing high heterogeneity (I 2 = 94.2%; p < 0.0001). The analysis of subgroups with BP showed high heterogeneity (I 2 = 94.2%; p < 0.01); interventions with PE presented more favorable results (I 2 = 0%; 0; p = 0.90); the sexual function instruments showed high heterogeneity (I 2 = 90%; p < 0.01); and instruments of quality of life and menopausal symptoms with domains of sexual function presented favorable results for BP and PE (I 2 = 0%; p = 0.63). The funnel chart presents the studies in a dispersed manner, which implies publication bias. Conclusions: Interventions with PE proved to be more efficient compared to BP, however, there are a low number of studies with PE, and those found are limited to aerobic training, without sufficient data on intensity, volume, and frequency. Further studies with PE are needed for the treatment of sexual function symptoms in order to more comprehensively describe their effect.